DOI: 10.11606/t.11.2019.tde-20191220-123512
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade de água no solo para porta-enxertos de citros em ecossistema de tabuleiro costeiro

Abstract: À administração do Centro pelo apoio desde o início do curso em fevereiro de 1994. A Robson Oliveira pela ajuda inestimável em todas as fases do trabalho. Ao colega e pesquisador Roosevelt M. Prudente pela cessão do experimento de porta-enxerto. A José Roque de Jesus pela realização das filmagens das trincheiras. A Paulo Sérgio Santos da Mota pelo apoio durante a realização dos trabalhos no Campo Experimental de Umbaúba -CEU. Aos funcionários do CEU, Gilberto, Acácio, Raimundo e Milton pela dedicação com que e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
4

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
6
0
4
Order By: Relevance
“…For instance, root distribution of five citrus rootstocks in a Gray Argisol of Coastal Tableland, [Volkamer lemon 'Palermo' and 'Catânia' (Citrus volkameriana Pasquale), 'Rangpur' lime (Citrus limonia Osbeck), 'Rough Florida' lemon (Citrus jambhiri Lush) and 'Cleopatra' mandarin (Citrus reshni Hort. ex Tan)], were spatially positioned on average 61% in the 0-0.20 m layer and 90% in the 0-0.40 m layer (Cintra et al, 1999). Similar results were obtained by Souza et al (2004), and Santana et al (2006), also in cohesive soils.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…For instance, root distribution of five citrus rootstocks in a Gray Argisol of Coastal Tableland, [Volkamer lemon 'Palermo' and 'Catânia' (Citrus volkameriana Pasquale), 'Rangpur' lime (Citrus limonia Osbeck), 'Rough Florida' lemon (Citrus jambhiri Lush) and 'Cleopatra' mandarin (Citrus reshni Hort. ex Tan)], were spatially positioned on average 61% in the 0-0.20 m layer and 90% in the 0-0.40 m layer (Cintra et al, 1999). Similar results were obtained by Souza et al (2004), and Santana et al (2006), also in cohesive soils.…”
Section: Introductionsupporting
confidence: 78%
“…Cohesive horizons in soils of the Coastal Tablelands, with massive structure and hard to extremely hard consistency when dry, affect water dynamics and the distribution of roots, which are highly sensitive to the presence of cohesion (Souza et al, 2008). Consequently, the depth of the plant root system is reduced, by either the resistance to penetration (Silveira et al, 2010) aggravated by soil drying, or poor aeration (Cintra et al, 1999(Cintra et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…In places where long drought periods occur, large root volume can be a negative characteristic. Cintra et al (1999; observed, in Northeastern Brazil, that the 'Cleopatra' mandarin and the 'Rough' lemon had large root systems, leading to accelerated use of the soil water stock and, consequently, to a longer period of hydric stress. However, studying 'Pera' orange trees, Cintra et al (2000) concluded that plant water loss depends also on leaf area and scion type.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of citrus, rootstocks are responsible for important characteristics of the plants, like tolerance to hydric stress, to high soil acidity, and to high aluminium saturation (Pace & Araujo, 1986;. Performance of rootstocks in a certain environment is related to total volume, configuration, lateral distribution and depth of the root system (Cintra et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation